Exploring Experiences of Sociolinguistic Inclusivity and Exclusivity in Mentorship: Experiences of ESL Pre-Service Teachers in Johannesburg - Muringani, Plaxedes (University of the Witwatersrand, Johannesburg, 2024)
Mentoring is recognized worldwide as an important foundation of teacher education and is central to the professional development of Pre-service teachers (PSTs). Despite this, globally, mentorship does not seem to achieve its goals, and PSTs often face challenges. The study was motivated by a global problem that persists—the exclusion of English second language speakers (ESL) PSTs during mentoring. Yet, in the African continent and the local literature, such problems have been given limited attention. Therefore, sociolinguistic inclusion or exclusion of ESL mentees in South Africa became the subject of my research. This descriptive case study aimed to explore ESL PSTs’ lived experiences of mentorship while on teaching practice at quintiles four and five high schools in Johannesburg by focusing on their social-linguistic inclusion and/or exclusion. The specific questions that this study sought to answer were what ESL PSTs’ perceptions of school-based mentorship are, what ESL PSTs regard as inclusive or exclusive mentoring practices, and how ESL PSTs’ experiences of mentorship made them feel sociolinguistically included and/or excluded during teaching practice (TP). Consequently, the theoretical framework of social inclusion and Hart’s model of participation were used as a lens to understand the experiences of the PSTs in this study. A qualitative research method was used to identify the experiences of the PSTs. Open-ended questionnaires were completed by 22 purposefully selected PSTs from different years of study, and four of the 22 PSTs participated in interviews. The questionnaires and semi-structured interviews were then analysed using an interpretive approach through inductive thematic analysis. The study found that PSTs have diverse understandings of school-based mentorship. They also understood that inclusive mentoring practices mean authentic participation and unconditional mentorship, while exclusionary mentoring practices are a denial of access and opportunity to participate in the community and discrimination against individuals. There is also evidence that some experienced sociolinguistic exclusion, some experienced sociolinguistic inclusion, and some experienced both exclusion and inclusion in the process of mentorship. v Therefore, the study recommends that the office responsible for TP and the English department in the university should take note of the exclusion in schools when ESL teachers teach in certain contexts and take the necessary actions to alleviate the situation. Policymakers should consider revising the separate curricula for English First Additional Language (FAL) and Home Language (HL) in the basic education system as the study confirmed that the FAL curriculum does not equip PSTs with competencies for the HL context, hence the exclusion. It is recommended that further research be conducted to get more in this area of research incorporating different variables.
A research report submitted in fulfillment of the requirements for the Master of Education, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; inclusion; exclusion; mentoring experiences; sociolinguistic identity; teaching practice; pre-service teachers; English second-language speakers; SDG-4: Quality education